Fabrikasi Perancah Berpori Hidroksiapatit dari Tulang Ikan Tenggiri dengan Alginat Sebagai Binder Alami: Sebuah Kajian Naratif - Siswoyo Siswoyo; Kumalasari Kumalasari; Sari Wulan; Fitri Afriani (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2020)
Porous scaffolding is an alternative solution developed to assist the bone therapy process. Hydroxyapatite (HAp) is a widely developed material into porous scaffolding because it has good biocompatibility. As a maritime country, Indonesia has high fisheries potential. One potential maritime product waste that could be synthesized into HAp is mackerel bone because it contains high amounts of CaO. This narrative describes a potential method for HAp synthesis from mackerel fish bones and a fabrication method that can be applied to a porous scaffold. Alginate is a natural ingredient from brown algae, which can be used as a porogen to synthesize porous HAp. Because it comes from maritime-based natural materials, algae are relatively safe and easy to produce in Indonesia. It is hoped that from this study, a more comprehensive picture can be obtained related to the development of HAp-based porous scaffolding from mackerel fish bones so that it can be considered for further development.